Perceptions of Village-Owned Enterprise Managers on The Use of QRIS As A Digital Payment Instrument - Kristina Setyowati; Sri Maryuni; Septyanto Galan Prakoso (Spirit Publik: Jurnal Administrasi Publik, 2025)
Technology development impacts all aspects of people's lives. Increasingly complex needs cause the choice of digital technology. Advances in technology and information also contribute to the development of the digital economy including the development of digital payment systems using QRIS among business managers and the community. This study aims to determine the perception of BUMDes managers in using the Quick Response Indonesian Standard (QRIS). The results showed that BUMDes managers consider QRIS very useful for the transaction process. Judging from the perception of convenience and flexibility, they feel that using QRIS is easier, practical, and flexible. Although there are some barriers related to internet networks or quotas that result in less stability and lack of interest in using QRIS. The suggestion given is the need to increase the diffusion of innovation (socialization or counseling) about QRIS to increase awareness.